Negative recollections regarding doctor–patient interactions among men receiving a prostate cancer diagnosis: a qualitative study of patient experiences in Japan - Takeo Nakayama; Masako Torishima; Michiko Urao; Shinji Kosugi (BMJ Open)
Objectives To explore the negative recollections of prostate cancer patients regarding the attitudes and language used by the doctors in delivering their diagnoses in Japan, in order to improve patient-centred communication.Design and setting This is a qualitative secondary analysis of the prostate cancer narrative data from the Database of Individual Patients’ Experiences-Japan archives. A thematic analysis was conducted regarding negative recollections of doctors’ words/attitudes when delivering a cancer diagnosis. Recruitment was based on maximum variation sampling. Participants were recruited from medical institutions, patient associations and through media advertisements.Participants Men with a diagnosis of prostate cancer (n=51).Findings Of the 51 participants, 17 had negative recollections of the doctors’ words/attitudes during the delivery of the cancer diagnosis. After thematic analysis, 11 categories emerged: ‘Surprised by the abrupt disclosure of the diagnosis’, ‘Displeased by the direct disclosure of the diagnosis to the patient in the absence of family members’, ‘Unable to accept the doctor’s negative words in the explanations’, ‘Unable to understand the doctor’s technical jargon’, ‘Distrust due to failure in diagnosis based on previous examinations’, ‘Aggrieved at the doctor’s unwillingness to allow questions’, ‘Dissatisfied with explanations involving facts only’, ‘Indignant over the unexpected disclosure of life expectancy’, ‘Unable to accept the doctor’s blame for the delay in the initial hospital visit’, ‘Uncomfortable with the usage of inappropriate metaphors’ and ‘Pessimistic thoughts despite optimistic explanations’.Conclusions It is clear that patients have recollections of a variety of negative experiences regarding the words/attitudes of their doctors at the time they received their prostate cancer diagnosis. Thus, the use of narrative data would facilitate the appropriate application of commonly used guidelines for the delivery of cancer diagnoses tailored to individual patients in clinical practice.